Social and psychological capital in relation to social well-being among university students in Maragheh: A cross-sectional study - Arman Latifi; Shahryar Mokhtary; Hossein Nemati; Ali Karimi Mirzanezam; Sara Rahimi (PLoS ONE, 2026)
Background Social Capital and Psychological Capital are important determinants of individuals’ Social Well-Being. However, limited evidence exists on how these factors interact among university students in Iran. This study aimed to examine the relationships between Social Capital, Psychological Capital, and social well-being among Iranian university students. Methods In this cross-sectional study, 460 students enrolled at universities in Maragheh County were selected using cluster sampling. Data were collected through self-reported questionnaires, including demographic information (age, gender, marital status, residence status, and parents’ education), the Psychological Capital Questionnaire, the Social Capital Questionnaire, and the social well-being Questionnaire, in accordance with ethical considerations. Data were analyzed using SPSS v24. Descriptive statistics summarized the sample characteristics. Pearson correlation coefficients were computed to assess relationships among variables. Multiple regression analysis was conducted to examine the predictive effects of Psychological Capital, Social well-being, and demographic factors (marital status, residence status, father’s education) on Social Capital, with a 95% confidence level. Results Psychological Capital (mean ± SD: 99.11 ± 17.82) was positively associated with both Social Capital (70.02 ± 11.17) and social well-being (60.07 ± 6.12). Among demographic variables, marital status, residence status, and father’s education were significantly related to Social Capital. Multiple regression analysis showed that social well-being, Psychological Capital, and students’ residence status together explained a moderate proportion (22%) of the variance in Social Capital. Conclusions The findings demonstrate significant positive relationships between Psychological Capital, social well-being, and Social Capital. Psychological Capital, social well-being, and students’ residence status together predicted 22% of the variance in Social Capital. These results highlight the importance of promoting Psychological and social well-being to enhance Social Capital among university students.